Effect of Soaking, Germination, and Roasting on Phenolic Composition, Antioxidant Activities, and Fatty Acid Profile of Sunflower (Helianthus annuus L.) Seeds - Chorpaka Thepthanee; Hua Li; Hu Wei; Cheunjit Prakitchaiwattana; Sirithon Siriamornpun (My University, 2024)
This study investigates the impact of soaking, germination, and roasting under various conditions on the phenolic content, antioxidant activities, and fatty acid profile of sunflower seeds of striped and black oil seed varieties. Ferulic acid emerged as the predominant phenolic acid across all samples. The study highlights the influence of different treatments and processing conditions on the levels of phenolic acids and flavonoids. Results revealed that soaking striped seeds for 24 h and roasting black oil seeds for 6 min exhibited the highest total phenolic content (TPC) and total flavonoid content (TFC). Antioxidant activities varied, with striped seeds soaked for 24 h demonstrating the highest ferric-reducing antioxidant power (FRAP) values, while black oil seeds roasted for 6 min exhibited superior 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) radical scavenging activity. Oleic acid and linoleic acid were identified as major fatty acids in all processed samples, with striped seeds germinated for 24 h and black oil seeds germinated for 48 h displaying the highest concentrations. Soaking led to a reduction in both unsaturated and saturated fatty acids in both varieties. Roasting further influenced fatty acid concentrations, with a significant increase in striped seeds after 5 and 6 h of roasting, followed by a gradual decrease. Our findings suggest that incorporating appropriate processing methods, such as soaking striped seeds for 24 h and roasting black oil seeds for 6 min, enhances the potential health benefits of sunflower seeds.
Keywords: Helianthus annuus; Roasting; Sunflower seed; Sunflower and Safflower Cultivation